Differential physiological responses of portuguese bread wheat (Triticum aestivum L.) genotypes under aluminium stress - García Oliveira, A.L.; Martins Lopes, P.; Tolra, R.; Poschenrieder, Charlotte; Guedes-Pinto, H.; Benito, C. (MDPI, 2016)
The major limitation of cereal production in acidic soils is aluminium (Al) phytotoxicity which inhibits root growth. Recent evidence indicates that different genotypes within the same species have evolved different mechanisms to cope with this stress. With these facts in mind, root responses of two highly Al tolerant Portuguese bread wheat genotypes—Barbela 7/72/92 and Viloso mole—were investigated along with check genotype Anahuac (Al sensitive), using different physiological and histochemical assays. All the assays confirmed that Barbela 7/72/92 is much more tolerant to Al phytotoxicity than Viloso Mole. Our results demonstrate that the greater tolerance to Al phytotoxicity in Barbela 7/72/92 than in Viloso Mole relies on numerous factors, including higher levels of organic acid (OAs) efflux, particularly citrate efflux. This might be associated with the lower accumulation of Al in the root tips, restricting the Al-induced lipid peroxidation and the consequent plasma membrane integrity loss, thus allowing better root regrowth under Al stress conditions. Furthermore, the presence of root hairs in Barbela 7/72/92 might also help to circumvent Al toxicity by facilitating a more efficient uptake of water and nutrients, particularly under Al stress on acid soils. In conclusion, our findings confirmed that Portuguese bread wheat genotype Barbela 7/72/92 represents an alternative source of Al tolerance in bread wheat and could potentially be used to improve the wheat productivity in acidic soils.